Distribution system analysis and automation - Gers, Juan (The Institution of Engineering and Technology, 2013)
A comprehensive guide to techniques that allow engineers to simulate, analyse and optimise power distribution systems which combined with automation, underpin the emerging concept of the "smart grid". This book is supported by theoretical concepts with real-world applications and MATLAB exercises.
Keywords: Electrical engineering.; Electric networks.; Smart power grids.; elektronické knihy; electronic books